Impact of intensively lowered low‐density lipoprotein cholesterol on deferred lesion prognosis. Issue 4 (29th May 2019) - Nakamura, Shun; Yamamoto, Takanobu; Teng, Yun; Matsumoto, Sawa; Kasano, Kensuke; Yoshiwara, Hirotaka; Hattori, Eijiro; Tokunaga, Takeshi; Yonetsu, Taishi; Hirao, Kenzo
Abstract: Objectives: The aim of this study was to investigate the impact of intensively lowered low‐density lipoprotein cholesterol (LDL‐C) level on the deferred lesion prognosis after revascularization deferral based on fractional flow reserve (FFR). Background: Lowering LDL‐C is associated with lower cardiovascular event rate, but its benefit on the deferred lesion prognosis has not been well evaluated. Methods: This retrospective, single‐center, observational study analyzed 192 deferred lesions with FFR value >0.80 in 192 patients with stable coronary artery disease. According to the first follow‐up LDL‐C level, they were assigned to the LOW group (<70 mg/dL) or the HIGH group (≥70 mg/dL). Deferred lesion failure (DLF) was defined as the composite of deferred lesion revascularization and deferred vessel myocardial infarction. Results: Of all participants, 61 and 131 patients were assigned to the LOW and the HIGH group, respectively. During the median follow‐up of 2.8 years, DLF occurred in 1 and 14 patients in the LOW group and the HIGH group (1.6% and 10.7%, log‐rank p = .043), respectively. The incidence of any unplanned revascularization was also significantly lower in the LOW group than in the HIGH group (3.3% vs. 14.5%, log‐rank p = .032). Conclusions: The incidence of DLF was significantly lower in the patients with LDL‐C < 70 mg/dL than in those with LDL‐C ≥ 70 mg/dL at the first follow‐up after FFR‐based deferral of revascularization.